2019
DOI: 10.1016/j.coemr.2019.06.012
|View full text |Cite
|
Sign up to set email alerts
|

The thyroid axis, prolactin, and exercise in humans

Abstract: The thyroid hormones thyroxine and triiodothyronine as well as the anterior pituitary hormone prolactin each serve vital roles in humans. When challenged by stressful situations, all of these hormones respond in an attempt to maintain homeostasis. One powerful stressor to invoke the release of these hormones is physical activity, that is, exercise. The thyroids and prolactin each have independent roles allowing the body to accommodate to exercise. But they also share an interrelation in their responses. Hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 31 publications
0
20
0
6
Order By: Relevance
“…The effect of exercise on HPT axis activity in humans varies with its duration; the increase of serum TSH, T4 and T3 concentrations during exercise are reverted during recovery ( 127 ). Depending on health state and physical condition, the response of HPT axis to exercise differs between men and women.…”
Section: The Hpt Axis In the Symphony Of Energy Homeostasismentioning
confidence: 99%
“…The effect of exercise on HPT axis activity in humans varies with its duration; the increase of serum TSH, T4 and T3 concentrations during exercise are reverted during recovery ( 127 ). Depending on health state and physical condition, the response of HPT axis to exercise differs between men and women.…”
Section: The Hpt Axis In the Symphony Of Energy Homeostasismentioning
confidence: 99%
“…Interestingly, three TWAS loci that were significant in digestive tissues were associated with PA phenotypes that are proxies for meal-time activity: PDXDC2P with TLA 6am-8am, RERE with TLA 6pm-8PM and KANSL1 with TLA 4pm-6pm ( Table 2 ). It was also known that multiple organs in the endocrine system produce hormones that regulate physiological functions of the body, which can have complex bidirectional relationships with PA 39–43 . Our TWAS analysis indicated that the genes associated with PA via the blood and immune system tended to also be associated with the digestive and endocrine systems, but do not usually overlap with the genes associated with the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Регуляция всех этих гормонов осуществляется согласно ме-ханизму отрицательной обратной связи в оси гипоталамус -гипофиз -щитовидная железа [20]. Факторы, оказывающие стимулирующее или подавляющее влияние на компоненты этой оси, представлены в таблице 1 [21].…”
Section: функция и регуляция гормоновunclassified